2013
DOI: 10.3928/01477447-20130724-24
|View full text |Cite
|
Sign up to set email alerts
|

3.0-Tesla MRI and Arthroscopy for Assessment of Knee Articular Cartilage Lesions

Abstract: The purpose of this study was to evaluate the ability of 3.0-Tesla magnetic resonance imaging (MRI) to accurately assess knee articular cartilage lesions. Sixteen patients who had knee 3.0-T MRI and underwent knee arthroscopy for partial meniscectomy were included. Three fellowship-trained sports medicine orthopedic surgeons reviewed all images. Articular lesions on MRI were graded from I to IV and compared with arthroscopic grading using the Outerbridge and the International Cartilage Repair Society (ICRS) cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…The arthroscopic correlations in the small subset of patients showed relatively comparable accuracy with previous studies, albeit with slightly lower sensitivities . This was promising, because the goal of this study was not to compare the DESS and DESS+PDFS findings with arthroscopy.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The arthroscopic correlations in the small subset of patients showed relatively comparable accuracy with previous studies, albeit with slightly lower sensitivities . This was promising, because the goal of this study was not to compare the DESS and DESS+PDFS findings with arthroscopy.…”
Section: Discussionsupporting
confidence: 60%
“…Consequently, the readers were not provided with patient history, reason for referral, and previous imaging and surgical findings. The specificities of diagnosing injuries of the meniscus, ligaments, and tendons were high, whereas the sensitivities of diagnosing such lesions were lower (especially in cartilage), which has been chronicled in previous studies . Of the two ACL tears observed in the nine patients, one was correctly identified by all readers, while a subtle tear was missed by all readers, leading to the lower 50% sensitivity.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Regarding the agreement of MRI reading, the inter-rater reliability between the two MRI measurements, which was performed by two blinded physicians, showed a high ICC of 0.812 (95 % CI 0.747; 0.862; p < 0.0005). Compared with other studies using the MRI for detecting pathology in the knee joint, such as evaluation of cartilage lesions [32] or predicting the reparability of meniscus tears [6], the inter-rater reliability was reported from 0.13 to 0.434, respectively. Camp et al [8] showed inter-rater reliability values of 0.843 for determining the tibial tubercle-trochlear groove (TT-TG) distance by MRI, which is comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Kernaussagen: was 2 pixels (220 Hz/pixel) for 2D-PDwFS and 1.3 pixels (340 Hz/ pixel) for 3D-PDwFS. [14].…”
Section: Mr Imagingmentioning
confidence: 99%